2018
DOI: 10.29252/nirp.ijpcp.23.4.394
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cognitive-Behavioral Hypnotherapy on Body Dysmorphic Disorder: Case Study

Abstract: Objectives This study examined the effect of cognitive behavioral hypnotherapy on Body Dysmorphic Disorder (BDD), depression, and disability of patients. Methods In this article, we present a single subject experimental design with multiple baselines. The subjects of the study were patients with BDD in Sanandaj city. Purposive sampling was used, and after obtaining diagnostic interview and qualifications of the study, subjects underwent the treatment process. The Yale-Brown Obsessive Compulsive Scale modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…An Iranian study using single-subject methodology found that CBT improved patient's BDD symptoms as well comorbid depression and disability (Abbarin et al, 2018). A case study of a single adolescent female patient found that intensive CBT and exposure/response prevention reduced levels of general anxiety and increased functioning (Neziroglu et al, 2018).…”
Section: Body Dysmorphic Disordermentioning
confidence: 99%
“…An Iranian study using single-subject methodology found that CBT improved patient's BDD symptoms as well comorbid depression and disability (Abbarin et al, 2018). A case study of a single adolescent female patient found that intensive CBT and exposure/response prevention reduced levels of general anxiety and increased functioning (Neziroglu et al, 2018).…”
Section: Body Dysmorphic Disordermentioning
confidence: 99%
“…Past research has positively (or negatively) associated body- and appearance-related guilt and shame with several disruptive (or adaptive/healthy) behaviors and cognitions. For instance, body guilt and shame have been positively related to negative affect (Castonguay et al, 2014), body dysmorphic symptoms (Abbarin et al, 2018; Weingarden et al, 2016), obsessive-compulsive symptoms (Weingarden et al, 2016), and depressive symptoms (Brunet et al, 2019; Castonguay et al, 2014). Conversely, guilt and shame have been negatively associated with physical activity (Castonguay et al, 2015) and positive affect (Brunet et al, 2019; Castonguay et al, 2014).…”
Section: Introductionmentioning
confidence: 99%